ADOPSI TEKNOLOGI PAKAN TERNAK PADA USAHA SAPI POTONG DI KARESIDENAN SURAKARTA - Shanti Emawati; Endang Tri Rahayu; Ginda Sihombing; Ayu Intan Sari (Universitas Sebelas Maret, 2009)
The research was conducted to determine characteristic relation of farmer with feed technology adoption and factors which influenced cattle farmer adoption toward feed technology. Research was done from April to Juni 2008, located in Surakarta district. Survey mmethods was done to collect primary data at the farm level and secondary data from related institution. Purposive sampling was applied to sellect farmers respondent. Pearson correlation test used to determine characteristic relation of farmer with feed technology adoption. Multiple linier regression analysis used to determine factors which influenced cattle farmer adoption toward feed technology. The result showed that based on pearson correlation test, stall-house range had significant relation (P<0.01) eith feed technology adoption, while family burden total had significant relation (P<0.05) with feed technology adoption. Based on multiple linier regression analysis showed that stall-house range had significant affect (P<0.01) toward feed technology adoption, while stall width had significant effect (P<0.05) toward feed technology adoption.